1997
DOI: 10.1074/jbc.272.6.3590
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation, Subcellular Localization, and Membrane Orientation of the Alzheimer's Disease-associated Presenilins

Abstract: Presenilins 1 and 2 are unglycosylated proteins with apparent molecular mass of 45 and 50 kDa, respectively, in transfected COS-1 and Chinese hamster ovary cells. They colocalize with proteins from the endoplasmic reticulum and the Golgi apparatus in transfected and untransfected cells. In COS-1 cells low amounts of intact endogeneous presenilin 1 migrating at 45 kDa are detected together with relative larger amounts of presenilin 1 fragments migrating between 18 and 30 kDa. The presenilins have a strong tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
187
5
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(215 citation statements)
references
References 51 publications
21
187
5
2
Order By: Relevance
“…Confocal microscopic analysis of cells without any treatment showed that CD44 was mainly localized to filopodia of the plasma membrane (Figure 3a). PS1 was abundant in the perinuclear region (Figure 3b) as previously reported (De Strooper et al, 1997). However, a small amount of PS1 was detected at the plasma membrane ( Figure 3b) and colocalized with CD44 partially (Figure 3c).…”
Section: Figure 1 Continuedsupporting
confidence: 54%
“…Confocal microscopic analysis of cells without any treatment showed that CD44 was mainly localized to filopodia of the plasma membrane (Figure 3a). PS1 was abundant in the perinuclear region (Figure 3b) as previously reported (De Strooper et al, 1997). However, a small amount of PS1 was detected at the plasma membrane ( Figure 3b) and colocalized with CD44 partially (Figure 3c).…”
Section: Figure 1 Continuedsupporting
confidence: 54%
“…g-Secretase is thought to be an internal protease that cleaves within the membrane-spanning domain of all its substrate proteins. g-Secretase (PS1/NTF) is localized at the plasma membrane in cells with extensive cell-cell contacts (36)(37)(38)(39)(40)(41). On the basis of this g-secretase distribution, it did not seem that g-secretase would naturally favor Notch over E-cadherin cleavage in the well-formed spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, stable cells transfected with the first series of mutant cDNAs (K306A, K306E, KL/AP, and MAK/3A cells) showed increased amounts of the full-length polypeptides, NTF and CTF ( Fig. 2A, top and bottom panels, lanes [5][6][7][8][9][10][11][12], and decreased levels of endogenous PS1NTF and CTF (Fig. 2B, lanes 5-12).…”
Section: Endoproteolytic Processing Of Ps2 With Cleavagementioning
confidence: 99%